Endothelin‐1 Induces Myofibrillar Disarray and Contractile Vector Variability in Hypertrophic Cardiomyopathy–Induced Pluripotent Stem Cell–Derived Cardiomyocytes. Issue 6 (11th November 2014) - Tanaka, Atsushi; Yuasa, Shinsuke; Mearini, Giulia; Egashira, Toru; Seki, Tomohisa; Kodaira, Masaki; Kusumoto, Dai; Kuroda, Yusuke; Okata, Shinichiro; Suzuki, Tomoyuki; Inohara, Taku; Arimura, Takuro; et al.
Abstract : Background: Despite the accumulating genetic and molecular investigations into hypertrophic cardiomyopathy (HCM), it remains unclear how this condition develops and worsens pathologically and clinically in terms of the genetic–environmental interactions. Establishing a human disease model for HCM would help to elucidate these disease mechanisms; however, cardiomyocytes from patients are not easily obtained for basic research. Patient‐specific induced pluripotent stem cells (iPSCs) potentially hold much promise for deciphering the pathogenesis of HCM. The purpose of this study is to elucidate the interactions between genetic backgrounds and environmental factors involved in the disease progression of HCM. Methods and Results: We generated iPSCs from 3 patients with HCM and 3 healthy control subjects, and cardiomyocytes were differentiated. The HCM pathological phenotypes were characterized based on morphological properties and high‐speed video imaging. The differences between control and HCM iPSC‐derived cardiomyocytes were mild under baseline conditions in pathological features. To identify candidate disease‐promoting environmental factors, the cardiomyocytes were stimulated by several cardiomyocyte hypertrophy‐promoting factors. Interestingly, endothelin‐1 strongly induced pathological phenotypes such as cardiomyocyte hypertrophy and intracellular myofibrillar disarray in the HCM iPSC‐derived cardiomyocytes. We then reproduced these phenotypes in neonatal cardiomyocytes from the heterozygous Mybpc3 ‐targeted knock in mice. High‐speed video imaging with motion vector prediction depicted physiological contractile dynamics in the iPSC‐derived cardiomyocytes, which revealed that self‐beating HCM iPSC‐derived single cardiomyocytes stimulated by endothelin‐1 showed variable contractile directions. Conclusions: Interactions between the patient's genetic backgrounds and the environmental factor endothelin‐1 promote the HCM pathological phenotype and contractile variability in the HCM iPSC‐derived cardiomyocytes.